1983
DOI: 10.1111/j.1471-4159.1983.tb08156.x
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Depletion in the Spinal Cord Gray Matter of Rats with Experimental Allergic Encephalomyelitis

Abstract: Norepinephrine and dopamine concentrations were determined by radioenzymatic assay in discrete gray matter regions of the spinal cords of rats with experimental allergic encephalomyelitis (EAE). Norepinephrine was depleted in most spinal cord regions of EAE rats compared with controls, whereas dopamine depletion in EAE rats was restricted to the cervical dorsal horn. There was a rostrocaudal gradient of norepinephrine reduction in the spinal cords of the EAE rats with most severe depletion in the lumbar region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…We did not see any effects following treatment with atomoxetine alone, suggesting that endogenous levels of NA are not sufficient to provide anti-inflammatory or neuroprotective effects. Since in some EAE studies, CNS levels of NA were shown to be reduced (Krenger et al 1986;White et al 1983), the lack of effect of atomoxetine could be due in part to sub-physiological NA levels during EAE, thereby explaining the need for further augmentation of NA using L-DOPS. Co-treatment of mice with L-DOPS and a NARI has previously been shown to increase brain NA levels over treatment with L-DOPS alone (Kato et al 1986).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We did not see any effects following treatment with atomoxetine alone, suggesting that endogenous levels of NA are not sufficient to provide anti-inflammatory or neuroprotective effects. Since in some EAE studies, CNS levels of NA were shown to be reduced (Krenger et al 1986;White et al 1983), the lack of effect of atomoxetine could be due in part to sub-physiological NA levels during EAE, thereby explaining the need for further augmentation of NA using L-DOPS. Co-treatment of mice with L-DOPS and a NARI has previously been shown to increase brain NA levels over treatment with L-DOPS alone (Kato et al 1986).…”
Section: Discussionmentioning
confidence: 88%
“…Several studies point to perturbation of CNS NA or NA signaling in EAE or MS. In one EAE study in dogs, CSF and WM NA levels were found increased during early time points but reduced during the clinical period (Khoruzhaia and Saakov 1975); while in rodents, brainstem and spinal cord NA levels were reduced (Krenger et al 1986;White et al 1983). In contrast, in MS patients, it was reported that NA levels are increased in CSF (Barkhatova et al 1998) which could represent a compensatory response to reduced adrenergic activation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…White et al [16], showed, that both NA and DA are depleted in the spinal cord of mice suffering from EAE. Similarly, Krenger et al [17], showed that during entire course of EAE levels of 5-HT and NA are reduced in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs with EAE, CSF NA levels were reported to change over the course of disease with initial increases followed by later decreases (Khoruzhaia and Saakov, 1975). In several studies, CNS tissue levels were reported to be decreased in spinal cords of EAE rats (White et al, 1983;Krenger et al, 1986Krenger et al, , 1989. The striatal levels of dopamine (DA) and serotonin were higher in EAE mice than controls; however, NA levels were not different (BalkowiecIskra et al, 2007).…”
Section: Introductionmentioning
confidence: 96%